(untitled) (Global Journal of Human-Social Science, 2023)
This study assessed the knowledge of upper basic social studies students in some selected social studies contents Specifically the study investigated the knowledge acquisition of upper basic two students in some junior secondary one JS I social studies curriculum contents 453 upper basic two social studies students from five randomly selected secondary schools were involved in the study Six JS I social studies curriculum contents were selected and assessed in the study The contents are family life culture meaning and history of social studies examination ethical concepts HIV AIDS and drug abuse An instrument titled Knowledge Assessment in Social Studies Contents KASSC was used to generate data for the study Descriptive analysis was used to analyze data obtained from the study